Influencing people for healthier and more sustainable travel behaviours using smart phone technology - Audrey de Nazelle (Frontiers Media S.A., 2015)
Background Air pollution is in the top 10 risk factors for mortality worldwide, and one of the greatest health challenges of urban living. Solutions to urban air quality problems require a combination of technological advancements and efforts to promote healthier and more sustainable behaviours. The growth in information and communication technology (ICT) innovations and use offers new approaches to tackle such problems. We propose a novel ICT-based method to raise awareness and promote behavioural changes to reduce air pollution emissions and exposures in urban populations. The technological innovation is embedded within transtheoretical model of behavioural change theory to address and assess most effectively the desired behavioural change. We applied this approach to travel behaviours, to encourage participants to 1) reduce their contribution to air pollution emissions and 2) increase their physical activity levels by considering their mode choice, and also 3) to reduce their exposures to air pollution by considering their route choice. Method An experimental pilot study was conducted over the summer of 2014 in London, UK. Thirty volunteers were tracked using the Moves tracking app on their personal smart phones during 5 days on two occasions. Data collected by Moves was then processed and combined with local air quality maps to estimate personal exposures to air pollution. Half of the volunteers were provided with personalized feedback on their exposures and contributions to air pollution. They were all interviewed three times: before, in-between, and after the tracking sessions. Their stage of change in their consideration of the 3 behaviours targeted were assessed before and after the experiment to estimate the potential for moving individuals towards healthier and more sustainable behaviours through the ICT-derived personalized feedback approach. Results The use of three related behavioural targets lead to some confusion in data interpretation and as a result, only data from the exposure target was analysed. Most participants (90%) were in pre-contemplation with regards to reducing air pollution exposures, meaning they had never considered a change in travel behaviour to decrease their exposures to air pollution. Following personalized feedback, 30% of the participants progressed towards contemplating a behaviour change in the future, while none of the participants in the control group changed. Conclusion There is clear potential to change people's awareness and guide them towards healthier and more sustainable behaviours using novel ICT methods and personalized feedback on impacts of behaviours. Further explorations are needed on precise personalized messages that might produce the greatest effect for stage of change transitions towards actual changes in behaviour.